Timing and magnitude of Southern Ocean sea ice/carbon cycle feedbacks - Stein, Karl (Proc Natl Acad Sci U S A, 2020)
The Southern Ocean (SO) played a prominent role in the exchange of carbon between ocean and atmosphere on glacial timescales through its regulation of deep ocean ventilation. Previous studies indicated that SO sea ice could dynamically link several processes of carbon sequestration, but these studies relied on models with simplified ocean and sea ice dynamics or snapshot simulations with general circulation models. Here, we use a transient run of an intermediate complexity climate model, covering the past eight glacial cycles, to investigate the orbital-scale dynamics of deep ocean ventilation changes due to SO sea ice. Cold climates increase sea ice cover, sea ice export, and Antarctic Bottom Water formation, which are accompanied by increased SO upwelling, stronger poleward export of Circumpolar Deep Water, and a reduction of the atmospheric exposure time of surface waters by a factor of 10. Moreover, increased brine formation around Antarctica enhances deep ocean stratification, which could act to decrease vertical mixing by a factor of four compared with the current climate. Sensitivity tests with a steady-state carbon cycle model indicate that the two mechanisms combined can reduce atmospheric carbon by 40 ppm, with ocean stratification acting early within a glacial cycle to amplify the carbon cycle response.